The Andean situation and the South American approach - Ramírez, Socorro (2007)
The first part of the article shows how the period of current transition in the Andean Community could lead to its liquidation or the redefinition of its meaning and scope.  The way in which South American dynamics could affect the fate of the CAN, according to whether the questions about energy and infra-structure widen the political-ideological fragmentation, or whether they stimulate a plural restructuring of regional integration, is discussed in the second part of this work.